2017
DOI: 10.1002/jmv.24806
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐based point‐of‐care testing for cost‐effective diagnosis of acute flavivirus infections

Abstract: Flavivirus infections are a serious healthcare concern in tropical and subtropical countries. Although well-established laboratory tests can provide early diagnosis of acute dengue or Zika infections, access to these tests is limited in developing countries, presenting an urgent need to develop simple, rapid, and robust diagnostic tools. Microfluidic Paper-based Analytical Devices (μPAD), are typically rapid, cost-effective, user-friendly, and they can be used as diagnostic tools for the diagnosis of these inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…In previous publications, a new type of POC test, the paper‐based analytical device, called PAD, was successfully developed for DENV NS1 proteins and specific IgM detection in various human biological samples. In both cases, the LOD was close to that obtained with a commercial rapid test …”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In previous publications, a new type of POC test, the paper‐based analytical device, called PAD, was successfully developed for DENV NS1 proteins and specific IgM detection in various human biological samples. In both cases, the LOD was close to that obtained with a commercial rapid test …”
Section: Discussionsupporting
confidence: 75%
“…It has previously been shown that the PAD sensitivity is generally lower than that for ELISA . Here, it has been necessary to concentrate the culture supernatant containing the PPs through a lyophilization step to obtain a specific signal from IgM‐positive samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The device consists of a large area at the top for sample collection either directly from blood or from plasma, followed by coating of the area with specific antibodies against both the DENV and ZIKV's NS1 protein (Bedin et al, 2017) using a custom-made application on a smartphone for results reading. The device consists of a large area at the top for sample collection either directly from blood or from plasma, followed by coating of the area with specific antibodies against both the DENV and ZIKV's NS1 protein (Bedin et al, 2017) using a custom-made application on a smartphone for results reading.…”
Section: On-chip Immunoassaymentioning
confidence: 99%
“…(C) A flow-free magnetic actuation platform for microfluidic ELISA test (Coarsey et al, 2019). (D) Paper-based microfluidic test for ZIKV NS1 and DENV detection (Bedin et al, 2017).…”
Section: Na Amplification In Microfluidic Systemsmentioning
confidence: 99%